Konsep Daur Belajar sebagai Implementasi Manajemen Kurikulum di Sanggar Anak Alam Yogyakarta - Muhammad Izzul Haq; Abdul Aziz (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to describe the learning cycle concept as an implementation of curriculum management at Sanggar Anak Alam (SALAM) Yogyakarta. Indonesia's curriculum policy nomenclature changes from year to year, however, Sanggar Anak Alam (SALAM) itself consistently carries out learning cycle-based curriculum practices as a form of research. This curriculum practice has been running since the inception of SALAM in 1988 until now. Researchers use a case study approach with a qualitative type of research. Data was obtained through interviews, observation and documentation. The data is then analyzed using condensation techniques, presenting the data until conclusions are drawn. The results of the research include first, SALAM holistic education is carried out through a learning cycle and is supported by activities such as the Monday Legi market and minitrip. Second, learning cycle-based curriculum management practices with curriculum planning, implementation and evaluation. Curriculum management through the learning cycle positions students as real subjects, choosing to carry out and achieve goals with the help of facilitators so that holistic education is achieved.